Eksplorasi faktor yang mempengaruhi motivasi knowledge sharing pengikut akun X @literarybase - Deria Ramadayanti; Roro Isyawati Permata Ganggi (Prodi S1 Ilmu Perpustakaan dan Informasi, Fakultas Ilmu Budaya, Universitas Diponegoro, 2025)
The development of social media has had an impact on the ease of human interaction and the sharing of knowledge. One of the social media platforms that is developing in Indonesia is Twitter. In 2022, Indonesian Twitter users reached 18.45 million. One Twitter account with many followers who have an interest in books, literature, and reading is @literarybase. This study aims to determine the motivation of @literarybase followers to carry out knowledge sharing. The method used in this study is a qualitative method with a phenomenological approach. Data gathered through observation and interviews. The data analysis method used is thematic analysis. The results of the study show that there are three themes that motivate followers of the @literarybase account to share knowledge, namely; (1) the freedom of followers of the @literarybase account to do what they want; (2) Increased competence of @literarybase followers; (3) Feelings of interrelationship between followers of the @literarybase account.